Experimental investigation on efficient carbon dioxide capture using piperazine (PZ) activated aqueous methyldiethanolamine (MDEA) solution in a packed column. (September 2017) - Khan, Anoar Ali; Halder, GN.; Saha, A.K.
Highlights: Experiments were conducted using flue gas from self-adapted coal fire boiler. CO2 capturing characteristics were determined for MDEA/PZ blends in packed column. Regeneration efficiency was maximum using MDEA/PZ blend of 28/2 compared to 20/10. Reboiler heat duty requirement was less for blend with higher MDEA concentration. The effects of various process parameters on specific absorption rate were investigated. Abstract: The rising proportion of anthropogenic CO2 and its several adverse effects in the atmosphere through global warming has become an issue of widespread attention to find out an effective and highly efficient CO2 capture technique towards mitigation of greenhouse gas emission. The current investigation characterizes on CO2 capture technique through post combustion method by means of aqueous (MDEA + PZ) blend as an absorbent to arrest the power plant exhaust. The absorption study has been executed in a packed column over extensive variation of temperature and CO2 partial pressure besides physicochemical properties viz. viscosity and density determination. The CO2 absorption and stripping performances are evaluated under the influence of various process parameters. In this study PZ plays a significant role of reaction rate accelerator through gradual increase in mass percentage from 2 to 10 wt% maintaining a constancy of the entire solvent strength of 30 wt% in aqueous blend. The highest specific rate of absorption and maximum CO2 loading attained in aqueous (MDEA + PZ) blend having the PZ ratio of 10 wt% are (30.16 × 10 −6 ) kmol m −2  s −1 and 0.78 mol CO2 respectively. The maximum regeneration efficiency of 92.24% has been observed in aqueous (MDEA + PZ) blend containing least PZ fraction (2 wt%). The necessary amount of heat energy for solvent regeneration of aqueous (MDEA + PZ) blend has also been calculated and the estimated reboiler heat duty is within a range of 3.0–4.1 MJ/kg CO2 . Hence, aqueous (MDEA + PZ) blend could be an effective absorbent for CO2 capture from flue gas through absorption-desorption process.